Seasonal and spatial variation in the macroparasite fauna of Arctic charr (Salvelinus alpinus L.) in Lake Norsjø, South-Eastern Norway - Henriksen, Ann-Cecilie (University of South-Eastern Norway, 2019)
Within freshwater systems, several factors contribute to aggregated distributions of parasites in fish. Niche segregation, individual feeding preferences, sex of the host, and water temperature are all examples of such factors. In this study, structural patterns of the macroparasite community of Arctic charr (Salvelinus alpinus L.) in Lake Norsjø, situated in South-Eastern Norway, was investigated. Arctic charr was sampled from three locations within Lake Norsjø (North, Mid and South) three times (May, July, September) in 2018. Skin, gills, fins, intestinal tract, and coelom of the fish were examined macroscopically for ecto- and endoparasites. From 236 examined fish, seven parasite species were identified to species level. In addition, one parasite group was identified to genus level, and two groups to phylum level. Generalised linear models were used to explore the effect of season, location, fish length and sex on the abundance of two individual parasite species, and two functional groups of parasites. Fish length was the most important predictor of infection in all models for endoparasites, where infection increased with increasing fish length. No such relationship was discovered for the ectoparasites. Two species of the class Cestoda displayed different abundance in fish from the three fishing periods. The fish from the locations Norsjø North and Mid had similar parasite infections, probably as a result of resembling habitats, fishing depth and fish size. The profundal location Norsjø South differed with considerably less endoparasite abundance, and smaller fish size. The pattern was opposite for the ectoparasites, with heavier infections in Norsjø South. According to the statistical models, the sex of the Arctic charr did not explain the differences in parasite infection for any of the parasite species or groups. publishedVersion